TRAINING ON UTILIZATION AND PRODUCTION OF BANANA STEM CHIPS AS AN UMKM IDEA - T.Edyansyah; Rico Nur Ilham; Muhammad Multazam; Amru Usman; Muttaqien; Tarmizi Abbas (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Gampong Pase Sentausa, Simpang Keuramat District, North Aceh Regency is a village with approximately 500 people, with most of them working as farmers. Gampong Pase Sentausa also has various potential natural resources that are quite potential to be developed such as banana plants. Banana plants are a potential garden crop of the Gampong Pase Sentausa community, but until now the Gampong Pase Sentausa community knows bananas which are used as snacks or sold in bunches while the leaves are used for wrapping containers for making cakes and so on, while the use of banana stems has so far only been used as animal feed. In fact, if seen from its benefits, banana stems have many benefits for human health, namely they can treat and cure various diseases including: as a detoxification of the digestive system, losing weight, controlling cholesterol and blood pressure, curing stomach acid, curing stomach acid, stabilizing blood sugar, and there are still many benefits of banana stems for health. On the other hand, the people of Gampong Pase Sentausa underestimate banana stems and have no economic value at all, so through the 2022 KKN-LPPM, Malikussaleh University students took the initiative to provide innovation training in the use and manufacture of Banana Stems into Banana Stem Chips (Gedebog Chips) so that banana stem stalks which so far have no economic value can be increased through innovation in making and processing Banana Stem stalks into Gedebog Chips as a snack food for children and adults. The innovation in making banana gedebog chips will provide added economic value for the Pase Sentausa Village Community. The materials and tools used to make banana gedebog chips are easy to obtain and the manufacturing process is very easy and can be done individually or in community groups, which can be used as one of the entrepreneurial activities for the people of Gampong Pase Sentausa, Simpang Keuramat District, North Aceh Regency.